Portal transmídia mundo do sítio: análise do projeto transmídia do Sítio do Picapau Amarelo e sua relação com as demais extensões da obra de Monteiro Lobato - Torres, Rubens Francisco (Universidade Federal de São Carlos, 2014)
Important Brazilian children's literature author, Monteiro Lobato created with his books of "Sítio do Picapau Amarelo" a universe that remains and influences the imaginary of Brazilian population until today. This universe is not restricted only to literature, it expanded also in other media over almost ninety years, through TV shows, comic books, movies, and other media. In 2011 became available online the portal "Mundo do Sítio", first transmedia project product based on the work of Lobato. Besides the portal, the design transmedia of the "Sítio" also features an animation, social networking pages and a physical themed space located in Mairiporã-SP. The present research attempts to identify how the current transmedia project was developed from a universe already known and how it leverages influences from other adaptations to reintroduce the "Sítio" to a new generation. To do this, we conducted initially a historical survey of all the productions with the brand of the "Sítio", since the publication of the books by Monteiro Lobato, and then, we analyze the portal and identify its main transmedia characteristics and their relationship with the other productions made with the brand. Transmedia design of the "Sítio" uses elements developed in other adaptations of the work of Lobato and continues the expansion of the fictional universe, re-creating your space and encouraging their users to experience a playful way of that universe. With the animation, the story is expanded; presenting new information about the universe without mischaracterize the main characteristics developed by Lobato. Through social networks, users participate actively, both to assess the functioning of the Portal and how to develop productions based on the universe of the "Sítio". Finally, the portal uses features present in the text of Lobato that work effectively in the development of a TransMedia narrative.
Keywords: Literatura infanto-juvenil; Narrativa transmidiática; Sítio do picapau amarelo; Convergência midiática; Lobato, José Bento Monteiro, 1882-1948; Portais da Web; Portais infantis; Transmedia storytelling; Media convergence; Child portals; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA